2015
DOI: 10.1021/acsinfecdis.5b00026
|View full text |Cite
|
Sign up to set email alerts
|

Oxa, Thia, Heterocycle, and Carborane Analogues of SQ109: Bacterial and Protozoal Cell Growth Inhibitors

Abstract: We synthesized a library of 48 analogs of the Mycobacterium tuberculosis cell growth inhibitor SQ109 in which the ethylene diamine linker was replaced by oxa-, thia- or heterocyclic species, and in some cases, the adamantyl group was replaced by a 1,2-carborane or the N-geranyl group by another hydrophobic species. Compounds were tested against Mycobacterium tuberculosis (H37Rv and/or Erdman), Mycobacterium smegmatis, Bacillus subtilis, Escherichia coli, Saccharomyces cerevisiae, Trypanosoma brucei and two hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 15 publications
3
35
0
Order By: Relevance
“…Hitting numerous targets has several repercussions in drug research and development. It broadens the antimicrobial spectrum, as reported for SQ109 52 , nitazoxanide 53 and 2-AI compounds 54 . Furthermore, it decreases the likelihood of selecting for resistant mutants.…”
Section: Discussionsupporting
confidence: 60%
“…Hitting numerous targets has several repercussions in drug research and development. It broadens the antimicrobial spectrum, as reported for SQ109 52 , nitazoxanide 53 and 2-AI compounds 54 . Furthermore, it decreases the likelihood of selecting for resistant mutants.…”
Section: Discussionsupporting
confidence: 60%
“…Mycolic acids and the MmpL3 protein are not present in S. aureus and E. coli, so it is likely that an alternative cellular process in these organisms is targeted by the investigated compounds. Similarly, it was reported that SQ109, an inhibitor of MmpL3 in M. tuberculosis, displayed bactericidal activity against Helicobacter pylori and Trypanosoma brucei, organisms lacking the mmpL3 gene (55,56). Another MmpL3 inhibitor, the pyrrole derivative BM212 (45), was also identified as a compound with good activity against Candida albicans (57).…”
Section: Discussionmentioning
confidence: 85%
“…Based on the HEK293 activity, the compound was selective for all four parasites but only showed a marginal window with respect to HEPG2 activity. SQ-109 has been extensively studied for T. cruzi , T. brucei brucei , and L. donovani ; therefore, further studies on this compound may be of limited benefit ( 63 , 64 ). MMV687248, a 3,5-disubstituted pyridine with an IC 50 of 1.05 μM against T. brucei brucei with a selectivity index (SI) of >20 against both HEK293 and HEPG2, is an interesting novel starting point for HAT drug discovery.…”
Section: Discussionmentioning
confidence: 99%